Highly diverse endophytic fungi from Serra do Amolar-Pantanal (Brazil) producing bioactive secondary metabolites against phytopathogens - Mayrhofer, Bárbara Fanaya; Iantas, Jucélia; Noriler, Sandriele Aparecida; Ponomareva, Larissa V.; Thorson, Jon S.; Rohr, Jürgen; Shaaban, Khaled A.; Glienke, Chirlei (Frontiers in Microbiology, 2024)
IntroductionThe exploration of new bioactive compounds for agricultural applications is critical for sustainable development. Endophytic fungi, particularly those from underexplored biomes in Brazil, represent a promising source of natural compounds. This study focused on isolation and bioprospecting endophytic fungi from the medicinal plant Vochysia divergens (Pohl), grown in Serra do Amolar (Brazilian Pantanal Biome), with an additional emphasis on conserving microbial biodiversity.Methods and resultsLeaves and petioles were collected from 18 V. divergens specimens, from which 293 endophytes were isolated and grouped by morphological characteristics into 91 phenotypes. One representative of each phenotype was selected for secondary metabolite extraction and taxonomic identification. Fungi belonging to 27 families and 32 different genera were identified, with Diaporthe, Phyllosticta, and Pseudofusicoccum as the most predominant. We also introduce and describe a new endophytic species, Diaporthe amolarensis. Multiple extracts inhibited mycelial growth of the phytopathogenic fungus Colletotrichum abscissum, with a superior effect compared to the fungicide control. These extracts were produced by Diaporthe amolarensis, Xylaria arbuscula, and Nemania primolutea. Additionally, the extract from one X. arbuscula isolate displayed moderate activity against the phytopathogen Phyllosticta citricarpa. HPLC-UV and HPLC-MS analyses of these most inhibitory extracts revealed natural products with beneficial potential that need characterization and to have their modes of action elucidated.DiscussionFinally, a very important contribution of this study was the ex situ conservation of the biodiversity of the Serra do Amolar, allowing future studies and biotechnological applications involving endophytes from this region.